A numerical modelling study of longwall face stability in mining thick coal seams in China. (2017) - Song, Gaofeng; Chugh, Yoginder P.; Wang, Jiachen
Longwall face failures remain a major ground control and safety hazard in Chinese coal mines. This paper develops a better scientific understanding of stress and displacement distribution in the face area through 2-D finite element modelling of a typical longwall face in China. The results show: 1) most of the yielding occurs in the upper part of the face; 2) most vertical displacement occurs near the upper part of the coal face, while most horizontal displacement occurs around the centre part; 3) most face falls should, therefore, occur in the upper part of the coal face; 4) face stability is most affected by the load carrying characteristics of caved gob; 5) increased loading capacity of shields has limited effect on the stress distribution ahead of the face; 6) currently used face plate pressure distribution does not have a major effect on the redistribution of stress in the face area.